A missing piece is found: a new species of Paepalanthus (Poales, Eriocaulaceae) and the puzzling relations of the campos rupestres mountaintop floras of eastern Minas Gerais, Brazil - Rocha, Luiz Henrique; Gonella, Paulo Minatel [UNESP]; Andrino, Caroline Oliveira (Pensoft Publishers, 2024)
Paepalanthus is a diverse genus characteristic of the campos rupestres, a megadiverse vegetation found on mountaintops of mainly quartzitic mountain ranges of central-eastern Brazil. Recent efforts on prospecting the biodiversity of Serra do Padre Ângelo, a small mountain complex in eastern Minas Gerais, yielded several new plant and animal species, highlighting the urgency of conservation actions towards this still unprotected area. Here, we describe yet another new species found in the campos rupestres of these mountains, Paepalanthus magnus, a mountaintop microendemic species morphologically similar to taxa found in the Espinhaço Range, over 200 km distant, a biogeographic pattern shared by several other species. The affinities of the new species are discussed, and we provide illustrations, photographs, and SEM photomicrographs of the seed. We also discuss the conservation status of the species, which is preliminarily assessed as Critically Endangered, reinforcing the urgent need to address the conservation of the unique biodiversity of Serra do Padre Ângelo.
Keywords: Atlantic Forest; endemism; João Pinto Formation; Serra do Padre Ângelo; threatened species